Disease acceptance versus health locus of control in people after nephrectomy because of the kidney cancer - Kurowska, Krystyna; Siekierska, Izabela (Pielęgniarstwo Chirurgiczne i Angiologiczne/Surgical and Vascular Nursing, 2013)
Aim of the study: to define the relation between disease adjustment and health locus of control in patients diagnosed with kidney cancer, as a determinant of returning to optimal health. Material and methods : The study was carried out among 81 patients, diagnosed with kidney cancer (surgical kidney removal), hospitalized in urology wards in Bydgoszcz hospitals. Disease adjustment was assessed using the Acceptance of Illness Scale (AIS) while health locus of control – using the Multidimensional Health Locus of Control (MHLC) version B, in Juczynski adaptation. Results : Examined patients differ among each other regarding disease adjustment and health locus of control. Men present higher results of disease acceptance and internal dimension. It has been shown that there is a relation between disease acceptance and internal dimension among patients before 50 years of age, and others’ influence dimension in patients before 70 years of age. Patients over 70 years of age have the lowest disease acceptance. Patients living in the country present a lower level of disease acceptance and external locus of control. Married patients and those with children have a higher level of disease acceptance and internal locus of control. People with secondary and higher education present the highest scores regarding disease acceptance and internal dimension. The most frequently expressed fear concerns loss of the second kidney. Patients with higher AIS results and high internal dimension results do not have problems with adjusting to the changes imposed by the disease. Conclusions : Received results may proclaim that disease acceptance, internal health locus of control and the sense that others have the influence on our health may be significant when it comes to recovery.